Production of Novel Ebola Virus-Like Particles from cDNAs: an Alternative to Ebola Virus Generation by Reverse Genetics - Watanabe, Shinji (American Society for Microbiology, 2004)
We established a plasmid-based system for generating infectious Ebola virus-like particles (VLPs), which contain an Ebola virus-like minigenome consisting of a negative-sense copy of the green fluorescent protein gene. This system produced nearly 10(3) infectious particles per ml of supernatant, equivalent to the titer of Ebola virus generated by a reverse genetics system. Interestingly, infectious Ebola VLPs were generated, even without expression of VP24. Transmission and scanning electron microscopic analyses showed that the morphology of the Ebola VLPs was indistinguishable from that of authentic Ebola virus. Thus, this system allows us to study Ebola virus entry, replication, and assembly without biosafety level 4 containment. Furthermore, it may be useful in vaccine production against this highly pathogenic agent.